The Use of Team Game Tournament Method to Improve the Students' Reading Comprehension - Safitri Nurchasanah (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2020)
The objective of this research was to know the effectiveness of Teams Games Tournament (TGT) method to improve the students’ reading comprehension at the eighth grades of SMP N 02 Jepara in the academic year 2018/2019 and also to help the English teachers more creative in teaching reading especially on reading comprehension at eighth grades of SMP N 02 Jepara in the academic year 2018/2019. This research was a true experimental design exactly Pretest-Posttest control group Design that involving two groups of classes. One group treated as the experimental class and the other group treated as a controlled class. In the experimental class, the researcher applied the Teams Games Tournament (TGT) and in controlled class, the researcher applied conventional teaching strategy. The population of this research was the eighth grades students of SMP N 02 Jepara which consisted of 320 students. The samples of the research consisted of 64 students which were taken by using simple random sampling, VIII F consisted of 32 students as experimental class and VIII E consisted of 32 students as a controlled class. There were two variables in this research: Teams Games Tournament (TGT) as the independent variable and students’ reading comprehension as the dependent variable. The instrument of this research was the reading comprehension test. In the reading test, the result of the data indicated that there was a significant difference between students’ post-test in both experimental and controlled class. In the experimental class, the total mean score of the post-test was 94.75 was greater than the total mean score in the controlled class was 77.25. From the t-test, the researcher found that the value of the t-test in the post-test was greater than the t-table (8.616 > 2.000). Based on the findings and the discussion of the research, the researcher drew a conclusion that the use of the Teams Games Tournament was effective to improve the students’ reading comprehension in the eighth grades of SMPN 02 Jepara.